2020
DOI: 10.1021/acsphotonics.0c00409
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Optical Nonlinearity at the Metal to Insulator Transition in Magnesium Thin Films

Abstract: We report resonantly enhanced and switchable third order nonlinearity in magnesium thin films. Utilizing an optical parametric oscillator as a tunable broadband light source, we find a highly wavelength dependent third harmonic conversion efficiency, exhibiting a 40-to 50-fold signal increase over the investigated wavelength range between 1300 and 1800 nm. We relate this unusually strong increase of the intrinsic magnesium material nonlinearity to resonant sp-interband transitions around 0.7 eV or 1770 nm in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In the work by Wolf et al, k-space imaging was utilized, which revealed the directionality of the emitted THG light. Kauranen and Zayats, Chen et al, Drechsler et al, Krauth et al, Metzger et al, and Wegener et al , have studied second-harmonic generation (SHG) and THG emission of plasmonic nanostructures depending on shape, material, spectral detuning, pulse duration, etc. However, in most of those cases, the local microscopic origin was also not spatially imaged but mostly derived by using linear or nonlinear optical simulations.…”
mentioning
confidence: 99%
“…In the work by Wolf et al, k-space imaging was utilized, which revealed the directionality of the emitted THG light. Kauranen and Zayats, Chen et al, Drechsler et al, Krauth et al, Metzger et al, and Wegener et al , have studied second-harmonic generation (SHG) and THG emission of plasmonic nanostructures depending on shape, material, spectral detuning, pulse duration, etc. However, in most of those cases, the local microscopic origin was also not spatially imaged but mostly derived by using linear or nonlinear optical simulations.…”
mentioning
confidence: 99%
“…Especially plasmonic optical sensing platforms are an emerging field of interest as they allow, for example, to detect hydrogen (H 2 ) via an optical readout without further need of electronics in highly explosive environments. , Such sensors rely on the used plasmonic materials to be highly sensitive to a hydrogen exposure. Predestined and frequently used materials to show such unique properties are, for example, magnesium (Mg), niobium (Nb), , yttrium (Y), , or palladium (Pd). The latter is typically used as a catalyst to split hydrogen molecules at the Pd surface and to allow further diffusion of hydrogen atoms into the attached hydrogen-sensitive layers.…”
mentioning
confidence: 99%